David Jasper, The Sacred Desert: Religion, Literature, Art, and Culture. - Byrne, Mark (Journal for the academic study of religion, 2005)
David Jasper, The Sacred Desert: Religion, Literature, Art, and Culture. Blackwell, Oxford, 2004, pp. 208, ISBN 1405119748 (Hbk), 1405119756 (Pbk)